1983
DOI: 10.1002/mus.880060506
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing paramyotonia congenita and myotonia congenita by electromyography

Abstract: Compound muscle action potential (CMAP) amplitudes, response to 2 Hz nerve stimulation, response to exercise and electromyographic needle electrode examination findings from the thenar muscles of two patients with paramyotonia congenita were compared with those from two patients with dominantly inherited myotonia congenita in warm (34 degrees C) and cold (20 degrees C) states. Cold induced a significant fall in CMAP amplitude, induced/worsened a significant decremental response to 2 Hz stimulation, and virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…In the two PMC patients, cooling induced a significant and persistent reduction of CMAP amplitude and area, in agreement with earlier electrophysiological results 19, 24. These patients had the R1448H and T1700_E1703del mutations, respectively, in the muscle sodium channel gene.…”
Section: Discussionsupporting
confidence: 90%
“…In the two PMC patients, cooling induced a significant and persistent reduction of CMAP amplitude and area, in agreement with earlier electrophysiological results 19, 24. These patients had the R1448H and T1700_E1703del mutations, respectively, in the muscle sodium channel gene.…”
Section: Discussionsupporting
confidence: 90%
“…23 Cold temperature-induced changes in CMAP amplitude have also been described as specifically separating HPP and PC. 24,26 In two members of a family with PC, cold temperature provoked decreases in both CMAP area and amplitude.24 By contrast, in a family with HPP there was only a mild temperature-related decrease in CMAP amplitude which was offset by a concomitant increase in CMAP area, similar to results reported for normal individuals.26 Because of the distinctly different responses which ran true within each family, it was suggested that HPP and PC were two distinct disorders.…”
Section: Discussionsupporting
confidence: 56%
“…Assessment of myotonic syndromes relies on the detection of myotonic discharges with needle electromyography (EMG). Several provocative tests using surface‐recorded muscle responses have been proposed to distinguish the main clinical phenotypes before the advent of molecular diagnosis: repetitive nerve stimulation,5, 6 short exercise,7, 8 long exercise,9, 10 or cold exposure 8, 11, 12. In a recent study, we showed that changes of the compound muscle action potential (CMAP) after a repeated short exercise and after a long exercise allowed to separate muscle channelopathies into five patterns (I‐V), linked to the main clinical phenotypes and to subgroups of ion channel mutations 13.…”
mentioning
confidence: 99%